Plasma Therapy for Medication-Related Osteonecrosis of the Jaws- A Case Report - Maryam Jalili Sadrabad; Elham Saberian (Case Reports in Clinical Practice, 2023)
Medication-related osteonecrosis of the jaw (MRONJ) is a side effect of anti-bone resorption medications. Nowadays antiresorptive medications like bisphosphonate and monoclonal antibodies like denosumab that have been prescribed for bone disorders and metastatic cancer are becoming increasingly common. Although these medications are quite efficient at reducing bone resorption, they can develop osteomyelitis and jaw necrosis as a side effect. A 65-year-old woman was referred to the Oral Medicine Department of Semnan University of Medical Sciences with diffuse bilateral mandibular osteonecrosis, with a history of osteopetrosis and under-treatment of bisphosphonate. This complication started after tooth extraction and without any healing 5 years ago. After 3 sessions of plasma therapy, obvious improvement was seen. A proper medical history and a routine oral examination before treating with any invasive dental treatment are necessary to avoid any medication-related osteonecrosis of the jaw or mucosal abnormalities.